PENGARUH CORPORATE SOCIAL RESPONSIBILTY TERHADAP PROFITABILITAS DAN VALUE CREATION DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MEDIASI - Choirul Amin; Hexana Sri Lastanti (Jurnal Akuntansi Trisakti, 2020)
The aim of this study is to determine the influence of Corporate Social Responsibility (CSR) on profitability and value creation by adding Good Corporate Governance (GCG) as mediating variable. Measurement of Corporate Social Responsibility (CSR) using the Kinder Lydenburg Domini (KLD) Social Ratings Data or Clarkson's (1995) RDAP Scale which is an indicator of assessment focused on stakeholders including environmental dimensions, dimensions of product quality , community relations dimensions, dimensions of diversity, as well as the dimensions of employee relations. Measurement of Good Corporate Governance (GCG) uses the Corporate Governance Perception Index (CGPI). Profitability is proxied by Return of Assets (ROA) while value creation is proxied by Economic Value Added (EVA). The study was conducted on companies that consistently received awards as Indonesia Most Trusted Companies in 2018 and 2019 by the Indonesian Institute for Corporate Governance (IICG) and were published in SWA Magazine. Using the purposive sampling method, a sample of 25 companies with a total of 50 annual reports, financial reports and sustainability reports was obtained. The results showed that Corporate Social Responsibility (CSR) had a positive and significant effect on profitability, but did not affect the value creation and Good Corporate Governance (GCG) were not able to mediate the influence of Corporate Social Responsibility (CSR) on profitability but were able to mediate the influence of Corporate Social Responsibility ( CSR) towards value creation.